Impact of MEK Inhibitor Therapy on Neurocognitive Functioning in NF1. (October 2021) - Walsh, Karin S.; Wolters, Pamela L.; Widemann, Brigitte C.; Castillo, Allison del; Sady, Maegan D.; Inker, Tess; Roderick, Marie Claire; Martin, Staci; Toledo-Tamula, Mary Anne; Struemph, Kari; Paltin, Iris; Collier, Victoria; et al.
Abstract : Background and Objectives: Neurofibromatosis type 1 (NF1)-associated cognitive impairments carry significant lifelong morbidity. The lack of targeted biologic treatments remains a significant unmet need. We examine changes in cognition in patients with NF1 in the first 48 weeks of mitogen-activated protein kinase inhibitor (MEKi) treatment. Methods: Fifty-nine patients with NF1 aged 5–27 years on an MEKi clinical trial treating plexiform neurofibroma underwent pretreatment and follow-up cognitive assessments over 48 weeks of treatment. Performance tasks (Cogstate) and observer-reported functioning (BRIEF) were the primary outcomes. Group-level (paired t tests) and individual-level analyses (Reliable Change Index, RCI) were used. Results: Analysis showed statistically significant improvements on BRIEF compared with baseline (24-week Behavioral Regulation Index: t (58) = 3.03, p = 0.004, d = 0.24; 48-week Metacognition Index: t (39) = 2.70, p = 0.01, d = 0.27). RCI indicated that more patients had clinically significant improvement at 48 weeks than expected by chance (χ 2 = 11.95, p = 0.001, odds ratio [OR] = 6.3). Group-level analyses indicated stable performance on Cogstate ( p > 0.05). RCI statistics showed high proportions of improved working memory (24-week χ 2 = 8.36, p = 0.004, OR = 4.6, and 48-week χ 2 = 9.34, p = 0.004, OR = 5.3) but not visual learning/memory. Patients with baseline impairments on BRIEF were more likely to show significant improvement than nonimpaired patients (24 weeks 46% vs 8%; χ 2 = 9.54, p = 0.008, OR = 9.22; 48 weeks 63% vs 16%; χ 2 = 7.50, p = 0.02, OR = 9.0). Discussion: Our data show no evidence of neurotoxicity in 48 weeks of treatment with an MEKi and a potential clinical signal supporting future research of MEKi as a cognitive intervention.